The global helium market. Production and consumption volumes, industry problems. Gazprom's role in the global helium market ("Journal "U". Economy. Management. Finance.", 2025)
The article examines the global global helium market, as well as the world's largest producers and consumers of helium. The main vectors of helium use are medicine and microelectronics. The main reasons for the helium shortage in recent history are given: the shortage of the first stage (2006-2007), which was completed in 2008 as a result of the commissioning of the first helium plant in Qatar and the global economic crisis (reduced demand for helium); the shortage of helium of the second stage (2011-2013), which was completed in 2013 as a result of the commissioning of the second helium plant in Qatar; the helium shortage of the third stage (2017-2020), which was completed as a result of the spread of Covid-19 (reduced demand for helium); finally, the helium shortage of the fourth stage (2022 –present) is due to the postponement of the launch of two of the three installations. purification, liquefaction and packing of helium at the Amur Gas Processing Plant of Gazprom Pererabotka Blagoveshchensk, PJSC Gazprom, and a significant increase in the cost of purchasing helium. Global events that influenced significant changes in the global helium market in 2022-2023 are reflected. Potential prospects for increasing the volume of production, sales and consumption of helium in the near future until 2030 are discussed. The special role of the Amur Gas Processing Plant Gazprom Pererabotka Blagoveshchensk, PJSC Gazprom, in meeting the growing helium needs was noted by commissioning two of the three helium fine purification, liquefaction and packaging plants in 2023, primarily for large consumers from the Asia-Pacific region.
Keywords: global helium market; helium shortage; helium manufacturers; iso container